2023
DOI: 10.3390/foods12163085
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Processing of White Grape Must as a Strategy to Reduce the Addition of SO2

Cristina Cejudo,
Ana Belén Díaz,
Lourdes Casas
et al.

Abstract: In winemaking, sulfur dioxide addition is the most common procedure to prevent enzymatic and microbial alterations. However, the enological industry looks for safer alternatives to preserve enological products, and high-pressure treatments with supercritical CO2 are a suitable alternative. This study evaluates the effectiveness of this process in the stabilization and preservation of white grape must, studying the influence of time, pressure, and CO2 percentage on must characteristics. In spite of the percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Cejudo et al [2] presented a study focusing on the influence of supercritical CO 2 treatment on stabilizing and storing white grape musts, addressing the influence of time, pressure, and CO 2 percentage on must characteristics. The results showed that the CO 2 level was the variable that most influenced the process and that the employed treatment did not significantly affect some key parameters, such as pH, acidity, and color intensity.…”
mentioning
confidence: 99%
“…Cejudo et al [2] presented a study focusing on the influence of supercritical CO 2 treatment on stabilizing and storing white grape musts, addressing the influence of time, pressure, and CO 2 percentage on must characteristics. The results showed that the CO 2 level was the variable that most influenced the process and that the employed treatment did not significantly affect some key parameters, such as pH, acidity, and color intensity.…”
mentioning
confidence: 99%